STRATEGI KOMUNIKASI PADA SINIAR “CURHAT BANG” DALAM KANAL YOUTUBE DENNY SUMARGO - Islamiah, Rahma Nadia; Pujiastuti, Rahayu (Bahtera Indonesia, 2025)
Communication carried out by sources and presenters in podcasts requires certain communication strategies so as not to cause misunderstandings when understanding the message. Based on this, the aim of this research is to describe the form of communication strategy in the "Curhat Bang" podcast broadcast on Denny Sumargo's YouTube channel, June 2023 edition. This research uses a qualitative approach with descriptive methods. The data for this research is in the form of the speakers' statements. The data source in this research is Denny Sumargo's "Curhat Bang" podcast, June 2023 edition. This research data was collected using documentation techniques, download techniques and observation techniques. The data analysis procedure is carried out by examining the data, transcribing, classifying and codifying, interpreting and concluding the results of data analysis. The validity of the data in this research is in the form of theoretical triangulation and method triangulation. The results of this research provide information that the communication strategies used in the "Curhat Bang" podcast broadcast on the June 2023 edition of Denny Sumargo's YouTube channel, namely (1) avoidance strategies, include avoiding topics and ignoring messages; (2) paraphrasing strategies, including approximations, creating new words, and rambling (description); (3) transfer strategy, including literal translation and code mixing; (4) strategy for requesting assistance; (5) strategy for using gestures (mime). Keywords: Communication strategy, Tarone concept, podcast.